THE ADMINISTRATION OF DAYAK ONION INFUSION EFFECTIVELY REDUCES PRIMARY DYSMENORRHEA - Raharjo, Rahmawati; Diana, Alis Nur (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Dysmenorrhea, or menstrual pain, is a common gynecological complaint among women. Dayak onion, which has traditionally been used as a remedy, has not yet been seen for its effectiveness in reducing primary dysmenorrhea in adolescent girls. The aim is to determine the effect of giving Dayak onion infusion on primary dysmenorrhea in adolescents. The type of research used is quasi-experimental with a design of One Group Pre-Test - Post-Test Design Without Control Group. The population is all adolescent girls in the Sumberseras Muncar Banyuwangi health center area in 2023, totaling 371 people, with a sample of 16 people. Sampling technique using simple random sampling. Data analysis using paired sample t-test. Characteristics of respondents aged 16 years (56.3%), menarche age 12 years (43.8%), and menstruation duration 7 days (50%). The level of primary dysmenorrhea before giving Dayak onion infusion, most of the respondents experienced severe menstrual pain with a total of 9 people (56.3%). The level of primary dysmenorrhea after giving Dayak onion infusion, most of the respondents experienced mild menstrual pain with a total of 12 people (75%). There was an effect of giving Dayak onion infusion on primary dysmenorrhea in adolescent girls (p-value: 0.000 <α: 0.05). There is an effect of giving Dayak onion infusion on primary dysmenorrhea in adolescent girls.